Luminescent nano-composites generated from a spray - Caiut, Jose Mauricio A. [UNESP]; Bazin, Laurent; Mauricot, Robert; Dexpert, Herve; Ribeiro, Sidney José Lima [UNESP]; Dexpert-Ghys, Jeannette (Elsevier B.V., 2008)
The spray-pyrolysis (SP) synthesis technique has been employed to obtain SiO2:Eu3+ and gamma-AlOOH:Eu3+, It was possible to obtain sub-micrometric spherical particles of SiO2 with luminescent Eu3+ ions bonded to the silica surface or embedded in amorphous silica beads, by controlling the synthesis and annealing process. Boehmite y-AlOOH doped with Eu3+ nanoparticles were synthesized by SP at moderate temperature (200 degrees C) with Eu3+ ions bonded to the surface hydroxyls of the boehmite nanocrystals. Luminescent nanocomposites were obtained by controlled reaction of gamma-AlOOH:Eu3+ nanocrystals with ASN (asparagine). In these nano-composites, the Eu3+ are held at the surface of the boehmite nanocrystals and partially shielded from interactions with additional luminescence quenchers (hydroxyl groups, water molecules). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Nano-composites; Nanoparticles; Optical properties; Luminescence; Silica; Rare-earths in glasses